Registration and Fusion of the Autofluorescent and Infrared Retinal Images. (14th September 2008) - Kolar, Radim; Kubecka, Libor; Jan, Jiri
Abstract : This article deals with registration and fusion of multimodal opththalmologic images obtained by means of a laser scanning device (Heidelberg retina angiograph). The registration framework has been designed and tested for combination of autofluorescent and infrared images. This process is a necessary step for consecutive pixel level fusion and analysis utilizing information from both modalities. Two fusion methods are presented and compared.